(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study examined effects of visual, auditory and kinesthetic learning strategy on interest of Basic School students in geometry, FCT Abuja, Nigeria. The study adopted a quasi-experimental pre-test, post-test control group research design. The target populations of this study comprised all JSSII students offering Mathematics in FCT Abuja. Two schools were randomly selected from the 2 Basic Schools in Gwagwalada Area Council and sixty (60) students were selected from each school using systematic sampling. The geometry Interest Inventory (GII) was adopted from Ritter and Marris in Jekayinfa, (2019) for interest testing before and after the treatment. The Geometry Interest Inventory (GII was administered) to both groups and their scripts were collected Data collected was analyzed using mean and standard deviation to answer the research questions, while Mann Whitney was used to test the hypotheses on interest. The study found that the VAK learning strategy have a positive impact on the interest of Basic schools’ students in FCT among others and recommendations were made that teachers should consider integrating VAK learning strategies into their teaching practices to enhance students’ interest and in Geometry.